A mini-review on Z and S scheme heterojunction bismuth based photocatalysts towards H2 production, CO2 reduction, and pollutant degradation - Arpita Paul Chowdhury; Kurupalya Shivram Anantharaju; Kempaiah Keshavamurthy; Swarnalata Swain; Bogegowda Uma (Next Materials, 2025)
Using the limitless energy of the sun, photocatalysis offers a sustainable and environmentally friendly way to clean up the environment and store energy. To overcome the drawbacks of traditional heterojunctions in terms of kinetics and thermodynamics, the step-scheme (S-scheme and Z scheme heterojunction was devised. Interestingly, because of their distinct electrical composition and layered architectures, bismuth-based catalysts have been extensively investigated in a variety of applications. Because the valence band of bismuth-based compounds is made up of hybrid orbitals, the band gap is less, making it easier to migrate photogenerated electron-hole pairs. This review's objective is to study the most recent developments and successes in the creation of Bi based S and Z scheme. First, a summary of the basic ideas behind the formation of heterojunctions was provided. Second, the important uses of S and Z scheme heterojunction photocatalysts in the creation of hydrogen, the reduction of CO2, and the degradation of pollutants were covered. Finally, the article provides valuable insights for future research and development involving in the designing and construction of a Bi-based heterojunction.